21st Century Multimedia Innovation: Development of E-LKPD Based On Scientific Inquiry in Science Class - Encep Andriana; Putri Syafiila Daffa Fauzany; Trian Pamungkas Alamsyah (Yayasan Keluarga Guru Mandiri, 2022)
This research explores learning 21st century that is oriented towards technological sophistication in the form of digital based multimedia innovation in Elementary School. This research that aims to find out how to develop, feasibility, and student response against e-LKPD based on scientific inquiry in Elementary School level science subject. This study uses research and development (RD) methods. In the collection of this research data using unstructured interviews, questionnaires, and documentation. Data analysis uses descriptive scale analysis. This development uses 4D model develop by Thiagarjan consists of 4 stages as Define, Design, Development, and Disseminate. Subject testing was conducted on 30 students of grade V Elementary School. The result namely validation of e-LKPD products based on scientific inquiry the results of material expert validators obtained an overall average of 95,38% into the category is very worthy, validation of linguists obtained an overall average of 96,36% into the category is very worthy, and media expert validation has obtained an overall average of 81,64% into the category is very worthy. The feasibility of e-LKPD products based on scientific inquiry science showed a positive respons from a student questionnaire result with an average percentage of 89,13% and 87,77%.